Precooling can prevent the reduction of self-paced exercise intensity in the heat - Duffield, R.; Green, R.; Castle, P.; Maxwell, N. (Medicine & Science in Sports & Exercise, 2010)
Purpose: This study investigated the effects of precooling on performance and pacing during self-paced endurance cycling in the heat and, further, the effects of cooling on contractile function as a mechanism for performance changes.